2015
DOI: 10.1111/aogs.12828
|View full text |Cite
|
Sign up to set email alerts
|

ST waveform analysis versus cardiotocography alone for intrapartum fetal monitoring: a systematic review and meta‐analysis of randomized trials

Abstract: Absolute effects of ST waveform analysis were minor, and the clinical significance of the observed reduction in metabolic acidosis is questioned. There is not enough evidence to justify the use of ST waveform analysis in contemporary obstetrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 44 publications
2
69
0
2
Order By: Relevance
“…We investigated several outcomes in our review, and two (risk of metabolic acidosis and operative vaginal delivery) showed statistically significant differences in favor of STAN. (3). Two other high quality meta-analyses were published almost simultaneously (4,5), and neither reported significant differences in rates of metabolic acidosis.…”
Section: Sirmentioning
confidence: 99%
“…We investigated several outcomes in our review, and two (risk of metabolic acidosis and operative vaginal delivery) showed statistically significant differences in favor of STAN. (3). Two other high quality meta-analyses were published almost simultaneously (4,5), and neither reported significant differences in rates of metabolic acidosis.…”
Section: Sirmentioning
confidence: 99%
“…Their conclusions, however, are based on presuppositions that are highly questionable. The systematic review by Blix et al (1) was prompted by a recently published American randomized controlled trial (RCT) on STAN (3). However, this RCT was performed on a predominantly low-risk population with guidelines for CTG interpretation and threshold for STAN intervention different from those applied in all European RCTs and in clinical use.…”
Section: Sirmentioning
confidence: 99%
“…However, subsequent multicentre trials, including the recently published large American STAN trial, could not reproduce these initial findings [59]. Recent meta-analyses show conflicting results regarding the decrease in metabolic acidosis, which indicates the need for more research [8,1013]. Meanwhile, Kwee et al [14] reported that the STAN monitor gives as many ST events in cases of proven uncompromised fetal condition as in situations with deteriorating fetal condition.…”
Section: Introductionmentioning
confidence: 99%